The Impact of Birth Order and Parenting Style on Sibling Rivalry Among Pre-school children - Suci, Helmanis (RRZ Scientific Publishing, 2023)
Sibling rivalry is an important aspect of child development and family dynamics, and understanding its prevalence, incidence, and risk factor is essential for addressing the potential negative effects on a child's emotional and social well-being. This study aims to determine the correlation between birth order and parenting style and sibling rivalry at Surau Gadang Subdistrict, Siteba, Padang City, Indonesia. A cross-sectional design was implemented. A simple random sampling technique was utilized for this research. Data analysis used univariate and bivariate. The results showed that more than half of the respondents (65.8%) whose parenting style was authoritarian experienced sibling competition. A total of 85 respondents to this study, with an average age of 37.2 years. We found that birth order (p-value=0.018), parenting style (p-value=0.040) have a significant correlation with sibling rivalry. Prior to becoming a parent, it is crucial to engage in thorough preparation. A health worker in a public health center should give information not only about health but also about parenting skills. Keywords: sibling rivalry, birth order, parenting style